FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2014 - Elyzabeth Missi Laurdika Simamora; Azwir Nasir; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to investigate the influence of company size, profitability, board size, firm age on the disclosure of corporate social responsibility. The sample used in this research is manufacturing companies listed on the Stock Exchange in 2014. The data used in this research is secondary data. The collection of data by the method of documentation, which is a means used to obtain data in the form of annual reports published by the companies sampled in the period 2014 on the website of the Stock Exchange (www.idx.co.id) by tracking the company's annual report were selected to be sampled research. As a guide then use the check-list or a list of questions yangt contains items responsibility disclosure sosial.Metode analysis of this study using multiple regression analysis using SPSS version 20.0. The results of this study indicate that the independent variables company size, profitability, board size has no significant effect on the disclosure of corporate social responsibility at a significant level (α)> 0.05, whereas the life of a significant effect on the disclosure of corporate social responsibility at the (α ) <0.05. Results ajusted R-Square-test of independent variables on the dependent variable was 42.1% While the remaining 57.9% is influenced by other variables not examined in this study.Keywords : Size, profitability, Commissioners, age, and Corporate social responsibility